Risk aversion and favorite-longshot bias in a competitive fixed-odds betting market - Karl Whelan (University College Dublin, UCD School of Economics, 2022)
Research on sports betting markets has generally found a favorite-longshot bias, the empirical pattern for loss rates for bets on longshots to be higher than for favorites, which implies the odds do not reflect the underlying probabilities. The existing literature focuses largely on pari-mutuel betting but favorite-longshot bias is also evident in fixed-odds online betting markets of the type that are growing rapidly around the world. Explanations for this bias in previous work on parimutuel markets cannot explain why it would be a feature of competitive fixed-odds betting markets. We show how disagreement among gamblers and risk-aversion on the part of bookmakers in a competitive market can produce a pattern of favorite-longshot bias resembling the empirical evidence.
Keywords: D81; G14; L83; 330; Sports Betting; Gambling; Favorite-Longshot Bias